Facies model of a fine‐grained, tide‐dominated delta: Lower Dir Abu Lifa Member (Eocene), Western Desert, Egypt. Issue 5 (21st May 2013) - Legler, Berit; Johnson, Howard D.; Hampson, Gary J.; Massart, Benoit Y.G.; Jackson, Chris A‐L.; Jackson, Matthew D.; El‐Barkooky, Ahmed; Ravnas, Rodmar; Uličný, David
Abstract Existing facies models of tide‐dominated deltas largely omit fine‐grained, mud‐rich successions. Sedimentary facies and sequence stratigraphic analysis of the exceptionally well‐preserved Late Eocene Dir Abu Lifa Member (Western Desert, Egypt) aims to bridge this gap. The succession was deposited in a structurally controlled, shallow, macrotidal embayment and deposition was supplemented by fluvial processes but lacked wave influence. The succession contains two stacked, progradational parasequence sets bounded by regionally extensive flooding surfaces. Within this succession two main genetic elements are identified: non‐channelized tidal bars and tidal channels. Non‐channelized tidal bars comprise coarsening‐upward sandbodies, including large, downcurrent‐dipping accretion surfaces, sometimes capped by palaeosols indicating emergence. Tidal channels are preserved as single‐storey and multilateral bodies filled by: (i) laterally migrating, elongate tidal bars (inclined heterolithic strata, 5 to 25 m thick); (ii) forward‐facing lobate bars (sigmoidal heterolithic strata, up to 10 m thick); (iii) side bars displaying oblique to vertical accretion (4 to 7 m thick); or (iv) vertically‐accreting mud (1 to 4 m thick). Palaeocurrent data show that channels were swept by bidirectional tidal currents and typically were mutually evasive. Along‐strike variability defines a similar large‐scale architecture in both parasequence sets: a deeply scoured channel belt characterized by widespread inclined heterolithic strata is eroded from the parasequence‐set top, and flanked by stacked, non‐channelized tidal bars and smaller channelized bodies. The tide‐dominated delta is characterized by: (i) the regressive stratigraphic context; (ii) net‐progradational stratigraphic architecture within the succession; (iii) the absence of upward deepening trends and tidal ravinement surfaces; and (iv) architectural relations that demonstrate contemporaneous tidal distributary channel infill and tidal bar accretion at the delta front. The detailed facies analysis of this fine‐grained, tide‐dominated deltaic succession expands the range of depositional models available for the evaluation of ancient tidal successions, which are currently biased towards transgressive, valley‐confined estuarine and coarser grained deltaic depositional systems.